Content Analysis of Vertical–Horizontal Relations in Surah Al-Baqarah 43 from the Perspective of the Kediri Tafsir - Safiatuddina Quthrunada; Afriza Syahrul Mubarak (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2025)
In general, a Muslim’s life has two main dimensions: the vertical dimension (the relationship with Allah) and the horizontal dimension (the relationship with fellow human beings). This study examines the role of social media, specifically the YouTube channel Tafsir Kediri, which presents an interpretation of Surah Al-Baqarah verses 42–43 by Dr. Abdur Rohman. The aim is to analyze a modern, millennial-oriented style of Qur’anic interpretation that still incorporates Javanese/Indonesian local wisdom. The method employed is content analysis, involving data selection, categorization, interpretation, and the drawing of conclusions. The results of the study indicate that: (1) the vertical and horizontal relationships in Islam are complementary; (2) prayer (?al?h) and almsgiving (zak?t) serve as the foundation of obedience as well as social harmony; and (3) a believer’s faith is also reflected in an attitude of caring for and protecting the environment as a trust from Allah.